The cobweb spiders of the genus Anelosimus Simon, 1891 (Araneae: Theridiidae) in Hainan Island, China - Zhang, Bao-Shi; Liu, Long; Zhang, Feng (Zootaxa, 2011)
Five species of the spider genus Anelosimus Simon, 1891 (Theridiidae) are reported from Hainan Island, China, including two new species: Anelosimus membranaceus n. sp. (male, female) and A. subcrassipes n. sp. (female). A. seximaculatum (Zhu, 1998) n. comb. is transferred from the genus Theridion Walckenaer, 1805. The male of A. seximaculatum and the female of A. chonganicus Zhu, 1998 are described and illustrated for the first time.